New species and new records of freshwater Chaetonotida (Gastrotricha) from Sweden - Kånneby, Tobias (Zootaxa, 2011)
Gastrotricha is a small phylum of acoelomatic aquatic invertebrates common in both marine and freshwater environments. The freshwater gastrotrich fauna of Sweden is poorly known and so far only 20 species have been reported. In this study two species, Heterolepidoderma joermungandri n. sp. and H. trapezoidum n. sp., are described as new to science. Moreover, 9 species are presented as new to the Swedish fauna. Additional taxonomic information is also given for 4 species previously reported from the country. In total 7 genera of two families, Chaetonotidae and Dasydytidae, are presented and the number of reported freshwater gastrotrichs from the country is increased to 31.